2010
DOI: 10.1021/jp102828g
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Decay of Fluorobenzene Radical Anions Affected by Their Isomeric Structures and the Number of Fluorine Atoms

Abstract: Aryl fluoride has attracted much attention as a resist component for extreme ultraviolet (EUV) lithography, because of the high absorption cross section of fluorine for EUV photons; however, less is known about electron attachment to fluorobenzene (FBz) and the stability of the reduced state. Picosecond and nanosecond pulse radiolysis of tetrahydrofuran solutions of FBz from mono-, di-, tri-, tetra-, penta-, and hexafluorobenzene was performed, and the effects of isomeric structure and number of fluorine atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 73 publications
(31 reference statements)
2
25
0
Order By: Relevance
“…It seems quite natural to choose the reaction coordinate method with the C–Hal bond elongation as the coordinate when Hal − elimination is studied, and there are a lot of examples of such choice in literature. For instance, the method of reaction coordinate was used when the decay of fluorobenzene RAs was examined and the data on dissociative electron attachment to dichlorobenzene isomers were interpreted . We can suppose that in both cases authors failed to describe completely and unambiguously the regularities observed because a real reaction coordinate may be much more complicated than bond elongation alone.…”
Section: Monomolecular Fragmentation Of Radical Anions Of the Halogenmentioning
confidence: 99%
“…It seems quite natural to choose the reaction coordinate method with the C–Hal bond elongation as the coordinate when Hal − elimination is studied, and there are a lot of examples of such choice in literature. For instance, the method of reaction coordinate was used when the decay of fluorobenzene RAs was examined and the data on dissociative electron attachment to dichlorobenzene isomers were interpreted . We can suppose that in both cases authors failed to describe completely and unambiguously the regularities observed because a real reaction coordinate may be much more complicated than bond elongation alone.…”
Section: Monomolecular Fragmentation Of Radical Anions Of the Halogenmentioning
confidence: 99%
“…[79][80][81] However, the development of high-absorption resists based on fluorinated polymers still requires further efforts, because the change in backbone polymers significantly affects acid generation, acid diffusion, catalytic chain reaction, and dissolution. 82,83) Recently, hafnium oxide resists have attracted much attention because of their high EUV absorption and etching resistance. 11,84) The hafnium oxide resist developed by Inpria showed 15 nm resolution (30 nm pitch) with 70 mJ cm À2 sensitivity.…”
Section: Absorption Enhancementmentioning
confidence: 99%
“…9−16 Pico-and nanosecond transient absorption measurements during pulse radiolysis provide kinetic and mechanistic information on formation and decay of the intermediates. 13,17,18 Mesolysis promoted by reductive electron transfer to a molecule AB with A and B groups linked by a σ-bond may be subjected to different mesolysis mechanisms. 5−7 One is the concerted mechanism where the electron attachment on AB occurs together with dissociation to A radical (A • ) and B anion (B − ).…”
Section: ■ Introductionmentioning
confidence: 99%